1986
DOI: 10.3109/02813438609014834
|View full text |Cite
|
Sign up to set email alerts
|

One Year's Incidence of School Accidents and Their Severity in a Swedish Municipality

Abstract: The aim of this one-year investigation of school accidents was to determine the incidence and severity and to calculate the proportion of school accident cases in relation to all accident cases and to estimate their medical care consumption. All patients were interviewed. The degree of severity was evaluated according to the Abbreviated Injury Scale (AIS). Case-histories and X-ray reports were examined. School accidents constituted five per cent of all accidents in the whole population (including grown ups). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
1
4
1
Order By: Relevance
“…Williams et al (1998) found in their study of sports injuries among Scottish adolescents that boys had a higher prevalence of injuries, as well as a higher severity (according to the AIS codes), than girls. Their finding concurs with other studies that conclude higher incident rates among boys (Zaricznyj et al, 1980; Jacobsson et al, 1986) as well as more severe injuries, than in girls (Sahlin, 1990). This dispersion is often explained by higher exposure time and intensity of male activities as well as a higher risk‐taking temperament.…”
Section: Discussionsupporting
confidence: 92%
“…Williams et al (1998) found in their study of sports injuries among Scottish adolescents that boys had a higher prevalence of injuries, as well as a higher severity (according to the AIS codes), than girls. Their finding concurs with other studies that conclude higher incident rates among boys (Zaricznyj et al, 1980; Jacobsson et al, 1986) as well as more severe injuries, than in girls (Sahlin, 1990). This dispersion is often explained by higher exposure time and intensity of male activities as well as a higher risk‐taking temperament.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, the mean AIS score found indicates that the injuries in this study were no! less severe than previously reported (19).…”
Section: Discussioncontrasting
confidence: 58%
“…In this study 50 injuries were reported during 39 school days. This rate corresponds to 19 in-juriesil000 student-years which is half the rate reported in recently published Nordic studies (2,3,9,18,19). Thus, an underreporting probably occurred.…”
Section: Discussionmentioning
confidence: 57%
“…However, girls are nearly twice as likely to be injured as boys at the school playground in Tucson, AZ, USA (10). In French schools, girls were injured during sports and physical training more often than boys (11), whereas in Swedish schools boys injured more often during sports and breaks (12). …”
Section: Introductionmentioning
confidence: 99%